Comparison of physical demands between matches and small-sided games in Australian Football - Wing, C.; Hart, N. H.; Ma`ayah, F.; Nosaka, K. (International Journal of Sports Science & Coaching, 2023)
This study evaluated the physical demands and specificity of small-sided games (SSGs) compared to matches in Australian Football (AF). Global positioning system (GPS) data was collected on 48 AF players from 39 matches and 28 training sessions across two seasons. Match data was analysed using the ball in play (BiP) method with the maximum BiP period for each match (e.g. the BiP with greatest meters per minute), for each variable (relative distance, high-speed running, and accelerations) averaged for each player to establish maximal means as reference points. Intensity of all BiP periods in matches and SSGs was compared (e.g. a BiP period recorded at 100 m·min-1 by a player with a maximal mean of 200 m·min-1, was classified as a 50% effort). This was categorised in 10% intensity buckets, and compared between matches and SSGs using linear mixed models and Cohen's d effect sizes. Distance was greater (p < 0.01) in the 20-49% buckets for matches and in the 60-89% buckets (p < 0.001) for SSGs. For high-speed running and accelerations, matches were greater (p < 0.001) in the 0-9% bucket but SSGs were greater (p < 0.001) in buckets from 20 to 49%. At the individual level, 37-49% of the players did not record any SSGs efforts in buckets of >80 to =90% across GPS variables. SSGs appear to provide a sub-optimal training stimulus, if the aim is to prepare AF players for the highest intensity periods of play recorded during matches, thus may under-prepare players for the intensity demands of AF matches.